2011
DOI: 10.1016/s1995-7645(11)60093-x
|View full text |Cite
|
Sign up to set email alerts
|

The post—treatment effects of enterobiasis on the occurrence of enuresis among children in Calabar, Nigeria

Abstract: This study is suggestive of the involvement of E. vermicularis in the aetiology of enuresis in Calabar. Children presenting with, especially, uncomplicated enuresis should be screened for enterobiasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 20 publications
1
12
1
Order By: Relevance
“…This may be due to crawling of adult female E. vermicularis around the perianal region for oviposition mainly during the early morning hours since it needs oxygen for laying the eggs. Out-Bassey et al (2011) showed the significant relation between anal itching as well as nail chewing behaviour of children and enterobiasis. The present finding coincides with result presented by Alo et al (2013) in Nigeria and Bustami and Khraish (2010) in Jordan where they have children having their nail biting habit was proportional to the prevalence of enterobiasis.…”
Section: Discussionmentioning
confidence: 92%
“…This may be due to crawling of adult female E. vermicularis around the perianal region for oviposition mainly during the early morning hours since it needs oxygen for laying the eggs. Out-Bassey et al (2011) showed the significant relation between anal itching as well as nail chewing behaviour of children and enterobiasis. The present finding coincides with result presented by Alo et al (2013) in Nigeria and Bustami and Khraish (2010) in Jordan where they have children having their nail biting habit was proportional to the prevalence of enterobiasis.…”
Section: Discussionmentioning
confidence: 92%
“…Pinworm infestation exists in 61.5 % of students with MNE in our study. Out-Bassey et al reported a significant difference in MNE between children with and without pinworm (53 vs. 34 %, respectively) in Nigerian school-age children [23].…”
Section: Discussionmentioning
confidence: 95%
“…It is well known that anthelmintic therapy is the most effective approach to control E. vermicularis infection [ 21 23 ]. The ideal therapeutic strategy is massive chemotherapy and repeated medication [ 24 , 25 ]. However, this study found that no mass-scale chemotherapy has been carried out in any school in the past year (data were collected from the director of each school).…”
Section: Discussionmentioning
confidence: 99%